Determinação simultanêa de pesticidas utilizando métodos eletroanalíticos e quimiométricos - Silva, Zilene Alves da (2011)
This paper describes the simultaneous determination of the pesticides paraquat and diquat using electroanalytical techniques coupled with chemometric methods. Although these two pesticides can be easily determined in trace levels, the same does not apply to mix due to a large overlap of the voltammetric peaks. For this reason it became necessary to treat the data obtained by square wave voltammetry with chemometric methods that used no current peaks, but all points of the voltammogram. In a first stage of work, the parameters were optimized voltammetric technique, the frequency of the pulse, amplitude and increased potential for using the design of experiments. In this step, for each analyte were used as a response to peak current, ip, and the first principal component, PC1. Both analysis procedures showed that the frequency of the pulse amplitude and the cross effect of these variables has a significant effect on the response of the system (ip or PC1). In a second step, the effect of the most significant variables were studied by response surface, which employed a planning CCD (central composite design of English) was optimized. It was then built an empirical model that correlates the response (ip or PCs) with the variables studied. The optimum values to obtain the best voltammetric response was frequency 170 s-1, amplitude 40 mV and scan increment of 2 mV. Finally, in a third stage of labor was performed to analyze the mixture of paraquat and diquat, applying the optimized parameters and transforming the voltammograms for the space of principal components. The quantification of the mixture of pesticides was performed using the Partial Least Squares Regression, PLS. The XII models developed had a RMSEP, 1,39 and 2,22 for paraquat and diquat for the correlation coefficients greater than 0.99, which demonstrates the efficiency of the methodology used.